Theoretical framework on management accounting and organisational change / Tuan Zainun Tuan Mat - Tuan Mat, Tuan Zainun (Universiti Teknologi MARA Cawangan Selangor, 2014)
Prior research in management accounting examined various relationships between organisational change and management accounting system (MAS). The purpose of this paper is to provide a theoretical framework by using contingency theory and institutional perspective about how organisational and MAS changes take place. This paper contributes to theoretical argumentation on the interrelationship between management accounting and organisational change and how such changes might help in achieving overall success of the organisation.